New studies in global IT and business service outsourcing 5th Global Scourcing Workshop 2011, Courchevel, France, March 14-17, 2011, Revised Selected Papers - Kotlarsky, Julia; Willcocks, Leslie; Oshri, Ilan (Lecture Notes in Business Information Processing, 2011)
This book contains 11 carefully revised and selected papers from the 5th Workshop on Global Sourcing, held in Courchevel, France, March 14-17, 2011. They have been gleaned from a vast empirical base brought together by leading researchers in information systems, strategic management, and operations. This volume is intended for use by students, academics, and practitioners interested in the outsourcing and offshoring of information technology and business processes. It offers a review of the key topics in outsourcing and offshoring, populated with practical frameworks that serve as a tool kit for students and managers. The topics discussed combine theoretical and practical insights, and they are extensively illustrated by case studies from client and vendor organizations. Last but not least, the book examines current and future trends in outsourcing and offshoring, paying particular attention to how innovation can be realized in global or outsourced software development environments.